Pre-service teachers uses of and barriers from adopting computer-assisted language learning (CALL) programs - Samani, Ebrahim; Baki, Roselan; Mohamed Razali, Abu Bakar (Australian International Academic Centre, 2014)
Success in implementation of computer-assisted language learning (CALL) programs depends on the teachers’ understanding of the roles of CALL programs in education. Consequently, it is also important to understand the barriers teachers face in the use of computer-assisted language learning (CALL) programs. The current study was conducted on 14 purposely selected pre-service teachers of Teaching English as second Language (TESL). The study examined: (1) What are pre-service teachers’ perceptions of the current use of CALL programs? (2) What are pre-service teachers’ major inhibitors of the implementation of CALL programs? The data for this study was collected through semi-structured interviews. The interviews were transcribed, and the transcription scripts were analyzed using qualitative data analysis software, i.e., hyper research version 2.8.3. Analysis of the data indicated that pre-service teachers were unsatisfied with their use of CALL programs, and they were also unsatisfied with their instructors’ use of CALL programs in their education. These pre-service teachers also believed that the bureaucracies regarding the use of CALL programs at their education institution are the main barrier to the successful implementation of CALL programs. In this regard, they also believed that these bureaucratic procedures in using CALL programs affected their instructors’ attitudes, and thus acted as a compounding barrier from the successful use of CALL programs. Other most frequent barriers that immerged in the context of this study include resources, lack of training workshops, lack of literacy, time. Findings of these studies will provide sufficient and conclusive information on the barriers from adapting CALL and ICT programs.